Evaluation and validation of laboratory procedures for the surveillance of ESBL-, AmpC-, and carbapenemase-producing Escherichia coli from fresh meat and caecal samples - Hendriksen, Rene S.; Cavaco, Lina M.; Guerra, Beatriz; Bortolaia, Valeria; Agersø, Yvonne; Svendsen, Christina Aaby; Nielsen, Hanne Nørgaard; Kjeldgaard, Jette Sejer; Pedersen, Susanne Karlsmose; Fertner, Mette; Hasman, Henrik (Frontiers in Microbiology, 2023)
Introduction Extended-spectrum β-lactamase- (ESBL) and AmpC- β-lactamase-producing Enterobacterales are widely distributed and emerging in both human and animal reservoirs worldwide. A growing concern has emerged in Europe following the appearance of carbapenemase-producing Escherichia coli (E. coli) in the primary production of food animals. In 2013, the European Commission (EC) issued the Implementing Decision on the monitoring and reporting of antimicrobial resistance in zoonotic and commensal bacteria. The European Union Reference Laboratory for Antimicrobial Resistance (EURL-AR) was tasked with providing two laboratory protocols for samples derived from meat and caecal content, respectively, for the isolation of ESBL- and AmpC-producing E. coli (part 1) and carbapenemase-producing (CP) E. coli (part 2). In this study, we describe the current protocols, including the preparatory work for the development. Methods Up to nine laboratory procedures were tested using minced meat as the matrix from beef, pork, and chicken as well as six procedures for the caecal content of cattle, pigs, and chicken. Variables included sample volume, pre-enrichment volume, pre-enrichment broth with and without antimicrobial supplementation, and incubation time/temperature. The procedures were evaluated against up to nine E. coli strains harboring different AMR genes and belonging to the three β-lactamase groups. Results and discussion The laboratory procedures tested revealed that the most sensitive and specific methodologies were based on a Buffered Peptone Water pre-enrichment of 225 ml to 25 g or 9 ml to 1 g for minced meat and caecal content, respectively, incubated at 37°C overnight, followed by inoculation onto MacConkey agar supplemented with 1 mg/L cefotaxime for detecting ESBL- and AmpC-producing E. coli and Chrom ID SMART (Chrom ID CARBA and OXA) for CP E. coli, incubated overnight at 37 and 44°C, respectively. We provided two isolation protocols for the EU-specific monitoring of ESBL- and AmpC- producing E. coli (part 1) and CP E. coli (part 2) from fresh meat (protocol 1) and caecal (protocol 2) samples, which have been successfully implemented by all EU Member States for the monitoring period 2014–2027 (EU 2020/1729).